2012
DOI: 10.3988/jcn.2012.8.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Itemized Hospital Charges for Acute Cerebral Infarction Patients Influenced by Severity in an Academic Medical Center in Korea

Abstract: Background and PurposeStroke imposes a major burden on patients, their families, and the national healthcare system. The purpose of this study was to determine the itemized hospital charges in acute ischemic stroke patients according to their severity by partitioning the charges in detail and then examining whether stroke severity was a significant contributor to these charges.MethodsThis study analyzed data of first-time acute ischemic stroke patients who had been admitted to an academic medical center betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…The results of our research indicated the possibility of overusing the limited health resources by some insured patients and the access to the health services might be unequal among different types of insured patients. Patients with death and transfer results had a higher cost due to the severity of illness [16]. Consistent with previous studies conducted in China, the charge was significantly higher at tertiary hospitals than for secondlevel hospitals [11,17,18].…”
Section: Discussionsupporting
confidence: 80%
“…The results of our research indicated the possibility of overusing the limited health resources by some insured patients and the access to the health services might be unequal among different types of insured patients. Patients with death and transfer results had a higher cost due to the severity of illness [16]. Consistent with previous studies conducted in China, the charge was significantly higher at tertiary hospitals than for secondlevel hospitals [11,17,18].…”
Section: Discussionsupporting
confidence: 80%
“…As demonstrated elsewhere [19, 22-24], LOHS was strongly, positively associated with inpatient charges for ischemic stroke. The average LOHS for our patients was 16 days and median LOHS was 14 days, considerably longer than that of other countries’ studies [12, 24, 25], which reported average LOHS values of 6–12 days.…”
Section: Discussionmentioning
confidence: 73%
“…The average LOHS for our patients was 16 days and median LOHS was 14 days, considerably longer than that of other countries’ studies [12, 24, 25], which reported average LOHS values of 6–12 days. Yoon et al [19] reported the acute ischemic stroke patients in Korea between 2003 and 2009, their study showed that the mean and median LOHSs were 15 and 10 days, respectively. Tu et al [23] studied the hospital charges for ischemic stroke in Japan between 1995 and 1999, they found that the mean (median) LOHS was 33 (30) days (range 2–155 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Among the clinical factors, the stroke severity has been identified as a major factor in the escalation of costs. [4][5][6][7][8][9][10] The ischemic stroke subtype classifications based on the underlying etiology can influence the treatment methods and process. [11] However, the observation in the earlier studies have been rather inconsistent with regard to the influence of stroke subtype on costs of acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%